Kontribusi Pola Asuh Orang Tua dan Kemandirian Belajar terhadap Hasil Belajar Pendidikan Agama Islam - Herawati, Susi; Hakim, Abdul; Munir, Muhammad; Nahayati, Nahayati; Marhamah, Marhamah (Universitas Indraprasta PGRI Jakarta, 2024)
This research was conducted to analyze the contribution of parenting patterns applied by parents and learning independence to PAI learning outcomes at SMAN 99 Jakarta. This type of research is quantitative with variables including the contribution of parenting styles, the contribution of independent learning and PAI learning outcomes. This research is descriptive quantitative research. The population of this study are 328 students in class X at SMAN 99 Jakarta. The sampling technique used 77 students using several data collection methods; questionnaires, documentation, observations, interviews and listerature studies. The data analysis technique used to answer the research hypothesis is multiple linear regression. The results of the research show that parenting styles contribute and have a positive relationship to the results of Islamic Religious Education at SMAN 99 Jakarta with a significant correlation coefficient value of t = 2.769 which is greater than t table of 1.992 and a significant level of Sig = 0.031. Learning independence contributes and has a positive relationship to Islamic Religious Education learning outcomes at SMAN 99 Jakarta, with a significant correlation coefficient = 2.264 which is greater than t table = 1.992 and a significant level of Sig = 0.042 and parenting style and student learning independence contribute together. on Islamic Religious Education learning outcomes at SMAN 99 Jakarta with a correlation coefficient value of fcount = 3.565, meaning it is greater than ftable (2.68) and the significant level is Sig. = 0.000.